2021
DOI: 10.3389/fimmu.2021.649693
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in the Pathogenesis of Rheumatoid Arthritis and Systemic Lupus Erythematosus: Same Foe Different M.O.

Abstract: Dysregulated neutrophil activation contributes to the pathogenesis of autoimmune diseases including rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Neutrophil-derived reactive oxygen species (ROS) and granule proteases are implicated in damage to and destruction of host tissues in both conditions (cartilage in RA, vascular tissue in SLE) and also in the pathogenic post-translational modification of DNA and proteins. Neutrophil-derived cytokines and chemokines regulate both the innate and adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 319 publications
(370 reference statements)
1
69
0
3
Order By: Relevance
“…This population is known as low-density neutrophils (LDNs) [ 50 ]. The LDN population was first described in SLE and RA [ 51 ] and has now been well characterized in both diseases [ 52 , 53 ]. The LDN population includes granulocytic/polymorphonuclear-myeloid-derived suppressor cells (PMN-MDSCs) with immunosuppressive properties and low-density granulocytes (LDGs), which are characterized as having proinflammatory effects [ 54 , 55 ].…”
Section: Neutrophil Heterogeneity In Chronic Inflammationmentioning
confidence: 99%
“…This population is known as low-density neutrophils (LDNs) [ 50 ]. The LDN population was first described in SLE and RA [ 51 ] and has now been well characterized in both diseases [ 52 , 53 ]. The LDN population includes granulocytic/polymorphonuclear-myeloid-derived suppressor cells (PMN-MDSCs) with immunosuppressive properties and low-density granulocytes (LDGs), which are characterized as having proinflammatory effects [ 54 , 55 ].…”
Section: Neutrophil Heterogeneity In Chronic Inflammationmentioning
confidence: 99%
“…A recent review discusses further differences between neutrophil phenotype in different disease with energy metabolism and glycolysis driving ROS and NET production in RA, while decreased redox reactions drive the same in SLE. [35] NET formation has an important role in the development and preservation of autoimmune diseases, organ damage in chronic inflammatory disorders and cancer. [36][37][38] In our study total neutrophils, LDN and NDN in patients with BD showed increased production of cfDNA compared with healthy controls when stimulated with PMA or E.coli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, anti-histone autoantibodies are also common in these patients [65]. In addition to anti-dsDNA and histone autoantibodies in SLE patients, autoantibodies against other NET components including high-mobilitygroup protein 17 (HMG-17), lamin B1, lamin B2, catalase, cathelicidin (LL37), apolipoprotein A, α-enolase, and annexin AI have been rarely detected [12,66]. It is also noteworthy that NET proteins in SLE patients can contribute to tissue damage.…”
Section: Slementioning
confidence: 99%
“…Following excessive NET formation and release of autoantigen, plasmacytoid dendritic cells (pDCs) can recognize the exposed autoantigens leading to interferon and autoantibody production, which are accompanied by tissue damage [12]. Therefore, regarding the pathologic role of NET formation, it has been considered more by researchers as an attractive therapeutic target [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation